2018
DOI: 10.1016/j.csbj.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Poly-sarcosine and Poly(Ethylene-Glycol) Interactions with Proteins Investigated Using Molecular Dynamics Simulations

Abstract: Nanoparticles coated with hydrophilic polymers often show a reduction in unspecific interactions with the biological environment, which improves their biocompatibility. The molecular determinants of this reduction are not very well understood yet, and their knowledge may help improving nanoparticle design. Here we address, using molecular dynamics simulations, the interactions of human serum albumin, the most abundant serum protein, with two promising hydrophilic polymers used for the coating of therapeutic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Recent results demonstrate that PEG harvests specific apolipoproteins as a result of preferential binding, which inhibit uptake and elimination by the MPS. [79][80][81] The harvesting effect is observed in the tendency of F2 and F3 to attract more proteins per lipid to the surface and form thicker corona layers than F1. They show that while protein enrichment is modulated by surface coatings, accumulation of stealth-mediating apolipoproteins is not dependent on PEG.…”
Section: Stealth-mediating Proteins Enrich On Liposomes Regardless Ofmentioning
confidence: 99%
“…Recent results demonstrate that PEG harvests specific apolipoproteins as a result of preferential binding, which inhibit uptake and elimination by the MPS. [79][80][81] The harvesting effect is observed in the tendency of F2 and F3 to attract more proteins per lipid to the surface and form thicker corona layers than F1. They show that while protein enrichment is modulated by surface coatings, accumulation of stealth-mediating apolipoproteins is not dependent on PEG.…”
Section: Stealth-mediating Proteins Enrich On Liposomes Regardless Ofmentioning
confidence: 99%
“…Recently, the interactions between PEG and individual amino acids have been quantified and applied to predict the extent of protein folding. Settanni et al simulated a mixture of PEG and plasma proteins such as serum albumin, transferrin, complement Cq1, and apolipoprotein A1, and calculated the local density of PEG near individual amino acids, the preferential binding coefficient of each peptide for PEG [59,60], and the conformation and thickness of PEG layer adsorbed on the protein surface [61], showing that PEG-protein interactions can be quantified by a simple model in terms of the solvent-accessible surface area exposed by each amino acid type on the protein surface, favorably compared with experimental results obtained by label-free proteomic mass spectrometry. Kurinomaru et al [62], Zaghmi et al [63], and Sindhu et al [64] found the effect of PEGylation on the structure, dynamics, and binding affinity of enzyme-therapeutic drugs such as α-amylase, glutamate dehydrogenase, and L-asparaginase, respectively.…”
Section: Proteinsmentioning
confidence: 99%
“…As shell material we chose either i) poly(ethylene glycol) (PEG), [ 25,32 ] ii) poly( N ‐2‐hydroxypropylmethacrylamide) (pHPMA) [ 18,33,34 ] or iii) polysarcosine (pSar), [ 35,36 ] as they are not only considered protein resistant but furthermore are part of drugs in preclinical or clinical investigations. [ 21,37–39 ] Moreover, all these polymers are hydrophilic and do not possess a net charge to reduce adsorption of proteins by electrostatic and hydrophobic interactions. [ 40,41 ] In addition, it was recently demonstrated that the pSar based nanoparticles maintain their diffusion coefficient and thus hydrodynamic radius even in full human blood.…”
Section: Introductionmentioning
confidence: 99%